Twenty-Seven-Year Follow-Up of Vietnam Air War USAF POWs and Matched Controls Not Captured: A Qualitative Study. Issue 1 (2nd January 2018) - Sledge, William; Rozanova, Julia; Dorset, Julianne
Abstract : Objective : To provide a follow up of a 1976 study of the impact of captivity on U.S. Air Force (USAF) POWs and USAF Controls matched for time in Southeast Asia, military rank and aircraft crew position. Method : Qualitative study of replies to open ended questions of positive and negative changes due to their captivity/combat experiences made by participants (POWs and Controls) who replied in both 1976 and in 2003. Results : Both groups acknowledged positive and negative effects of the experiences in 1976. In 1976 and 2003 the POWs mainly reported negative effects on career and family domains but positive effects of individual development and growth. Controls reported mild negative effects on family in 1976, and benefits to their careers and sense of self in both 1976 and 2003. Conclusion : Captivity during the Vietnam War for USAF included two types of extreme duress which were the incarceration itself; and the repatriation experience which entailed re-assimilation despite loss of occupation and disrupted families. Despite these obstacles, POWs exhibited substantial resilience in achieving self-growth and how they regarded themselves psychologically in comparison to their matched control fellow aviators who while also suffering a lesser separation from family, tended to prosper in their careers and were proud of their accomplishments. Long term separation from work, family and friends and the inability to return to their families and careers with the effectiveness demanded by their ambition were a more devastating ongoing consequence of their captivity than the immediate suffering of their imprisonment.